OLDER ADULTS' SUBJECTIVE WELL-BEING EXPERIENCING THE EXERGAME "I AM DOLPHIN". Issue 1 (31st December 2023) - Drazich, Brittany F.; Crane, Breanna M.; Taylor, Janiece L.; Szanton, Sarah L.; Moored, Kyle D.; Eldreth, Dana; Ahmad, Omar; Krakauer, John W.; Resnick, Barbara; Carlson, Michelle C.
ABSTRACT: The objective of this study was to understand older adults' perceptions of the connections between an exergame intervention, "I Am Dolphin, " and their subjective well-being. Researchers conducted three focus groups with 14 older adults who participated in the exergame feasibility study. The semi-structured focus groups were transcribed, coded, and analysed using deductive and inductive techniques. Three themes were constructed related to playing the exergame and participants' subjective well-being: 1) elevated mood (through scheduled activity, immersion, and socialization), 2) feelings of achievement (especially following frustration and competition), and 3) perceived cognitive or physical changes. These findings will help researchers better understand how exergames may relate to the well-being of older adults. Future investigators could use these findings to create and implement new exergame interventions.